Blocking the CGRP Receptor: Differences across Human Vascular Beds - Tessa de Vries; Deirdre M. Boucherie; Antoon van den Bogaerdt; A. H. Jan Danser; Antoinette MaassenVanDenBrink (MDPI AG, 2023)
Multiple drugs targeting the calcitonin gene-related peptide (CGRP) receptor have been developed for the treatment of migraine. Here, the effect of the small-molecule CGRP receptor antagonist zavegepant (0.1 nM-1 µM) on CGRP-induced relaxation in isolated human coronary arteries (HCAs) was investigated. A Schild plot was constructed and a pA2 value was calculated to determine the potency of zavegepant. The potency and Schild plot slopes of atogepant, olcegepant, rimegepant, telcagepant, ubrogepant and zavegepant in HCAs and human middle meningeal arteries (HMMAs), obtained from our earlier studies, were compared. Zavegepant shifted the concentration-response curve to CGRP in HCAs. The corresponding Schild plot slope was not different from unity, resulting in a pA2 value of 9.92 ± 0.24. No potency difference between HCAs and HMMAs was observed. Interestingly, olcegepant, atogepant and rimegepant, with a Schild plot slope < 1 in HCAs, were all >1 log unit more potent in HMMAs than in HCAs, while telcagepant, ubrogepant and zavegepant, with a Schild plot slope not different from unity, showed similar (<1 log difference) potency across both tissues. As a Schild plot slope < 1 may point to the involvement of multiple receptors, it is important to further identify the receptors involved in the relaxation to CGRP in HCAs, which may be used to improve the cardiovascular safety of future antimigraine drugs.